Pengaruh Sistem Informasi Akuntansi Dan Standar Akuntansi Pemerintah Terhadap Kualitas Laporan Keuangan Daerah: (Studi Empiris Pada Kabupaten Sijunjung) - Isramirathul Wahyu; Siska Yulia Defitri; Nidia Anggreni Das (OPTIMAL Jurnal Ekonomi dan Manajemen, 2022)
This study aims to examine the Effect of Accounting Information Systems and Government Accounting Standards on the Quality of Financial Reports (empirical study on Sijunjung Regency). While the research sample is the Head, Treasurer, and Financial Staff in the OPD (Regional Apparatus Organization) Sijunjung Regency, amounting to 81 respondents. The type of data used is primary data. The sampling technique used is total sampling by distributing questionnaires.The results showed that the Accounting Information System (X1) had an effect on the Quality of Financial Statements (Y). This result is evidenced by the significance value of t of 0.000 < 0.05. while the Government Accounting Standards (X2) affect the Quality of Financial Statements (Y).